Priorities for research in child maltreatment, intimate partner violence and resilience to violence exposures: results of an international Delphi consensus development process - Wathen C; MacGregor Jennifer CD; Hammerton Joanne; Coben Jeffrey H; Herrman Helen; Stewart Donna E; MacMillan Harriet L (BMC, 2012)
Abstract Background Intimate partner violence (IPV) and child maltreatment (CM) are major global public health problems. The Preventing Violence Across the Lifespan (PreVAiL) Research Network, an international group of over 60 researchers and national and international knowledge-user partners in CM and IPV, sought to identify evidence-based research priorities in IPV and CM, with a focus on resilience, using a modified Delphi consensus development process. Methods Review of existing empirical evidence, PreVAiL documents and team discussion identified a starting list of 20 priorities in the following categories: resilience to violence exposure (RES), CM, and IPV, as well as priorities that cross-cut the content areas (CC), and others specific to research methodologies (RM) in violence research. PreVAiL members (N = 47) completed two online survey rounds, and one round of discussions via three teleconference calls to rate, rank and refine research priorities. Results Research priorities were: to examine key elements of promising or successful programmes in RES/CM/IPV to build intervention pilot work; CC: to integrate violence questions into national and international surveys, and RM: to investigate methods for collecting and collating datasets to link data and to conduct pooled, meta and sub-group analyses to identify promising interventions for particular groups. Conclusions These evidence-based research priorities, developed by an international team of violence, gender and mental health researchers and knowledge-user partners, are of relevance for prevention and resilience-oriented research in the areas of IPV and CM.